Subjective Sexual Well-Being in Chilean Adults: Evaluation of a Predictive Model - Vera-Villarroel, P; Contreras-Ramirez, D; Lillo-Vidal, S (Routledge, 2016)
Research on sexuality has traditionally focused on sexual satisfaction, with studies into subjective sexual well-being being a recent phenomenon. This study sought to evaluate the relationship between sexual behavior, happiness, health, and subjective sexual well-being. The data were collected from 862 people aged between 18 and 50 years in Santiago, Chile, and were analyzed by logistic regression analysis. The results showed that sexual behavioral indicators (sexual frequency, sexual caresses, and touching), happiness, and perception of health taken as a whole predicted 47.4% of subjective sexual well-being (SSWB). Analysis of the four items of subjective sexual well-being separately showed that the dimension of physical satisfaction was associated with three variables of sexual behavior indicators with a prediction percentage of 33.5%, whereas emotional satisfaction was associated with three variables of sexual behavior indicators and happiness, with a percentage of prediction of 43.3%. Satisfaction with sexual function was associated with perception of health and one sexual behavior indicator, with a prediction percentage of 29.2% of this variable. The importance of sex was associated with three sexual behavior variables that predicted 26.2% of this variable. The results confirm that subjective sexual well-being can be predicted and that its four dimensions present a different behavior compared to the study predictors. © 2015, Copyright © Taylor & Francis Group, LLC.